A nanostructural view of the cell wall disassembly process during fruit ripening and postharvest storage by atomic force microscopy. (May 2019) - Posé, Sara; Paniagua, Candelas; Matas, Antonio J.; Gunning, A. Patrick; Morris, Victor J.; Quesada, Miguel A.; Mercado, José A.
Abstract: Background: The mechanical properties of parenchyma cell walls and the strength and extension of adhesion areas between adjacent cells, jointly with cell turgor, are main determinants of firmness of fleshy fruits. These traits are modified during ripening leading to fruit softening. Cell wall modifications involve the depolymerisation of matrix glycans and pectins, the solubilisation of pectins and the loss of neutral sugars from pectin side chains. These changes weaken the cell walls and increase cell separation, which in combination with a reduction in cell turgor, bring about textural changes. Atomic force microscopy (AFM) has been used to characterise the nanostructure of cell wall polysaccharides during the ripening and postharvest storage of several fruits. This technique allows the imaging of individual polymers at high magnification with minimal sample preparation. Scope and approach: This paper reviews the main features of the cell wall disassembly process associated to fruit softening from a nanostructural point of view, as has been provided by AFM studies. Key findings and conclusions: AFM studies show that pectin size, ramification and complexity is reduced during fruit ripening and storage, and in most cases these changes correlate with softening. Postharvest treatments that improve fruit quality have been proven to preserve pectin structure, suggesting a clear link between softening and pectin metabolism. Nanostructural characterisation of cellulose and hemicellulose during ripening has been poorly explored by AFM and the scarce results available are not conclusive. Globally, AFM could be a powerful tool to gain insights about the bases of textural fruit quality in fresh and stored fruits. Highlights: Cell wall disassembly and loss of middle lamella occurs during fruit softening. Nanostructural properties of wall components can be characterised by AFM. A loss of pectin complexity, length and branching, correlates with softening. Postharvest treatments that reduce softening preserve pectin structure. AFM visualisation of cellulose and hemicellulose is strongly influenced by the extraction procedure.